SAT0458 Rituximab in the Treatment of Children with Systemic Lupus Erythematosus: Analysis of 12 Patients. (23rd January 2014) - Alekseeva, E.; Denisova, R.; Valieva, S.; Bzarova, T.; Isayeva, K.; Sleptsova, T.; Mitenko, E.; Chistyakova, E.; Fetisova, A.
Abstract : Background: Treatment of childhood systemic lupus erythematosus (SLE) is an ongoing problem because of the severity of the disease in some patients and the side-effects of the currently available immunosuppressive agents. B-cell depletion might be useful and effective treatment for this disease according to researches in adults. Objectives: To assess the clinical and basic serological consequences of rituximab treatment in patients with systemic lupus erythematosus who have failed conventional immunosuppression Methods: An open study of 12 patients with severe SLE followed for a minimum of 6 months is reported. Half of patients (7 out of 12), 12 months follow-up data are described. Disease activity in these patients was assessed every 6 months using the SELENA SLEDAI, System Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index and estimates of anti-double-stranded DNA antibodies and serum C3, C4 levels, number of CD20 B lymphocytes. During the follow-up period, significant side-effects were sought and the reduction in oral prednisolone was recorded too. Background therapy included cyclophosphamide, plasmapheresis, intravenous immunoglobulin, methylprednisolone pulse therapy, mycophenolate mofetil. Rituximab was given 375mg/m 2 weekly, №4. All patients were treated with prednisolone and immunosupressive agents. Results: 11 patients were female and 1 male. At the initiation of rituximab treatment the mean age was 14.6 yr (range 10–17.5) and the mean disease duration was 3.6 yr (range 0.3–13.2). 5 had lupus nephritis. All parameters improved from in 6 months after rituximab treatment: the SELENA SLEDAI score from 16 (range 4-25) to 3 (range 0-14) (p=0.002), SLICC/ACR Damage Index from 3, 5 (range 0-6) to 2 (range 0-4) (p=0.02), serum C4 from 0, 13 (range 0, 01-0, 9) to 0, 24 (range 0.06-1.25) (p=0.04) (normal range 0.14 - 0.47 g/l) and double-stranded DNA binding from 73, 5 (range 0-250) to 8, 9 (range 0-130) (p=0.04) (normal range 0 - 20 ME/ml) (p=0.05). B-lymphocyte depletion was observed in all patients in the peripheral blood after 6 months (p=0.007). The mean daily prednisolone dose fell from 0.8 mg/kg (range 0.4-1.5) to 0.5 mg/kg (range 0.2-0.8). Proteinuria was improved in 5 patients from 5.6 gr/day (range 0.3-15) to 1.7 gr/day (range 0.3-5.0) (p=0.06). In 12 months rituximab treatment all parameters also improved in 7 patients. There were no flares follow up period. Serious Adverse events were registered: pneumonia (n=2), neutropenia (n=5), herpes Zoster infection (n=2), hypogammaglobulinemia (n=8). Conclusions: In this open study of patients who had failed conventional immunosuppressive therapy, considerable utility in the use of B-cell depletion has been demonstrated. Our data provide strong support for the performance of a full doubleblind control trial. Disclosure of Interest: None Declared